Anti-Cholera toxin activity of selected polyphenols from Careya arborea, Punica granatum, and Psidium guajava - Charla, Rajitha; Patil, Priyanka P.; Patil, Vishal S.; Bhandare, Vishwambhar V.; Karoshi, Veeresh; Balaganur, Venkanna; Joshi, Rajesh K.; Harish, Darasaguppe R.; Roy, Subarna (Frontiers in Cellular and Infection Microbiology, 2023)
Careya arborea, Punica granatum, and Psidium guajava are traditionally used to treat diarrhoeal diseases in India and were reported to show anti-Cholera toxin activity from our earlier studies. As polyphenols are reported to neutralize Cholera toxin (CT), present study investigated the inhibitory activity of selected polyphenols from these plants against CTB binding to GM1 receptor using in silico, in vitro, and in vivo approaches. Molecular modelling approach was used to investigate the intermolecular interactions of selected 20 polyphenolic compounds from three plants with CT using DOCK6. Based on intermolecular interactions, two phenolic acids, Ellagic acid (EA) and Chlorogenic acid (CHL); two flavonoids, Rutin (RTN) and Phloridzin (PHD) were selected along with their respective standards, Gallic acid (GA) and Quercetrin (QRTN). The stability of docked complexes was corroborated using molecular dynamics simulation. Furthermore, in vitro inhibitory activity of six compounds against CT was assessed using GM1 ELISA and cAMP assay. EA and CHL that showed prominent activity against CT in in vitro assays were investigated for their neutralizing activity against CT-induced fluid accumulation and histopathological changes in adult mouse. The molecular modelling study revealed significant structural stability of the CT-EA, CT-CHL, and CT-PHD complexes compared to their respective controls. All the selected six compounds significantly reduced CT-induced cAMP levels, whereas EA, CHL, and PHD exhibited > 50% binding inhibition of CT to GM1. The EA and CHL that showed prominent neutralization activity against CT from in vitro studies, also significantly decreased CT-induced fluid accumulation and histopathological changes in adult mouse. Our study identified bioactive compounds from these three plants against CT-induced diarrhoea.